Flight Attendant Training Program Evaluation Based on Kirkpatrick Model - Chandra Sagul Haratua Gultom; R. Madha Komala; Maruf Akbar (Nusantara Science and Technology Proceedings, 2020)
Training assessment is a necessary endeavor if businesses want to assume that the training they offer has a beneficial effect on employee success and the organization as a whole. This study was conducted to elicit knowledge about flight attendants in the program creation phase at the Angkasa Training Center in Jakarta. This study attempts to analyze program execution beginning with the response, learning, behavior, and performance, which includes assessing the program's effectiveness, implementing the program, and assessing the program's effects. Interview tools and Focus Group Discussion (FGD) techniques were used to collect data. Inter-views with flight attendant students, training participants' supervisors, and fellow trainees, specifically flight attendant students, were performed. The following are the findings of this study: 1). The level of appraisal of student reactions to the organizing committee and resource persons is very strong. You need just to focus on the planning of materials at the start of the session. 2) Evaluation of learning, specifically the ability of students' behaviors, abilities, and skills to have a significant assessment, 3). The behavioral assessment, namely the implementation of the evaluation, is conducted after the subjects return to their respective work environments. There was a substantial difference in behavior improvement during the pre-and post-training periods. Changes in behavior such as attendance discipline, dress code, driving, peer motivation, effective coordination, accuracy, and pace at which everyday activities are completed 4) Evaluation of the effect, specifically, there is a rise in the work of training graduates. Alumni will teach, mentor, and extend the experience learned through training to their colleagues, allowing for the development of more effective training approaches.